AKTIVITAS ANTIOKSIDAN DAN KOMPONEN BIOAKTIF PADA SELADA AIR (Nasturtium officinale L . R. Br) - Ella Salamah; Sri Purwaningsih; Ellis Permatasari (Jurnal Pengolahan Hasil Perikanan Indonesia, 2011)
Watercress (Nasturtium officinale L. R. Br) is aquatic plant that grown across mainland Europe and Asia. Beside as food  watercress also as help detoxify the liver, purify the blood and improve digestion. Research about properties of watercress for human health is still not fully elucidated. This research was aimed to measure rendement, chemical content of watercress, bioactive compounds, antioxidant activity and peroxide number of watercress and its parts (leaves and stems). The yield of leaves and stems were 23.43% and 59.38%, respectively. Water, protein, lipid, ash, acid insoluble ash and carbohydrate contents obtained from proximate analysis were 94.64%, 2.11%, 0.22%, 1.14%, 0.29% and 1.90%, respectively. Based on phytochemical test, watercress contained alkaloids, steroids/triterpenoids, phenols hydroquinone, carbohydrates and free amino acids. Test of antioxidant activity using DPPH method resulting IC  of the extract of intact watercress, leaves and stems were 337.32 ppm, 331.39 ppm and 439.10 ppm, respectively. The leaves extract has been shown to reduce the peroxide number of 0,8mg eq/kg bulok. Keywords: antioxidant, bioactives compounds, peroxide number, proximate, watercress.